2011
DOI: 10.1371/journal.pone.0017868
|View full text |Cite
|
Sign up to set email alerts
|

FGF19 Regulates Cell Proliferation, Glucose and Bile Acid Metabolism via FGFR4-Dependent and Independent Pathways

Abstract: Fibroblast growth factor 19 (FGF19) is a hormone-like protein that regulates carbohydrate, lipid and bile acid metabolism. At supra-physiological doses, FGF19 also increases hepatocyte proliferation and induces hepatocellular carcinogenesis in mice. Much of FGF19 activity is attributed to the activation of the liver enriched FGF Receptor 4 (FGFR4), although FGF19 can activate other FGFRs in vitro in the presence of the coreceptor βKlotho (KLB). In this report, we investigate the role of FGFR4 in mediating FGF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
168
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(179 citation statements)
references
References 37 publications
11
168
0
Order By: Relevance
“…7B ). In hepatocytes and liver cancer cells, FGF19 has been shown to signal through FGFR4 ( 31 ). In line with these fi ndings, we found that the 3 cell lines expressed signifi cantly high levels of FGFR4 mRNA ( Fig.…”
supporting
confidence: 83%
“…7B ). In hepatocytes and liver cancer cells, FGF19 has been shown to signal through FGFR4 ( 31 ). In line with these fi ndings, we found that the 3 cell lines expressed signifi cantly high levels of FGFR4 mRNA ( Fig.…”
supporting
confidence: 83%
“…Strong FGFR4 mRNA was detected in hepatocytes adjacent to central vein by in situ hybridization, and the hepatic dysplasia foci and BrdU labeling from FGF19 transgenic livers are also located around central vein. In addition, activation of FGFR4 alone was sufficient to induce hepatocyte proliferation (Wu et al, 2010a;Wu et al, 2010b) and FGF19 induced hepatocytes proliferation was not observed in FGFR4 knockout mice, confirming the role played by FGFR4 in hepatocarcinogenesis (Wu et al, 2011).…”
Section: Fgf Pathwaymentioning
confidence: 79%
“…This occurs in the liver via activation of hepatic FGFR4, hence completing a negative feedback loop on bile acid synthesis ( 16 ). In addition, FGF19 has been shown to affect expression of other Cyp enzymes that may lead to alterations in bile acid pool composition ( 17 ). However, given that the elimination of cholesterol is primarily through conversion to bile acids and subsequently excreted, FGF19 treatment would be expected not only to reduce bile acid levels but also to increase cholesterol levels.…”
Section: Serum Triglyceride Cholesterol and Bile Acids Measurementmentioning
confidence: 99%
“…FGF19 activates FGFR4, which is predominantly expressed in the liver, and activation of this receptor by FGF19 has been shown to reduce the bile acid pool size ( 16,25 ) and affect bile acid composition ( 17 ). This pathway has been proposed as the enterohepatic signal that mediates postprandial inhibition of bile acid synthesis ( 16,25 ).…”
Section: Acute Fgf19 Treatment Also Increased Plasma Tg Levels In Diementioning
confidence: 99%